2015
DOI: 10.13189/ijccd.2015.030401
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Resuscitation Performance: Study on the Effectiveness of Training and Support at a Teaching Hospital in KSA

Abstract: Introduction: This paper discussed nurses' resuscitation trainings and their performance in a teaching hospital based on AHA guideline recommendations. The study explored the current standard practices and investigates the nurses' views on the effectiveness of the training, quality of equipment, familiarity and readiness of nurses in performing resuscitation. Methodology: A cross-sectional descriptive study conducted at teaching hospitals which mandate all nurses must be certified with the BLS and attends two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
0
0
3
Order By: Relevance
“…Equally, studies done by ( 5,10,55,56,57,58), all con rm the similarity of the results as reported where there is signi cant difference between pretest and posttest as well as retention test between the two methods in this review. Only one study by (28) reported a contrary view of studies done by ( 59…”
Section: Acquisition and Retention Of Skills After Cpr Trainingsupporting
confidence: 81%
“…Equally, studies done by ( 5,10,55,56,57,58), all con rm the similarity of the results as reported where there is signi cant difference between pretest and posttest as well as retention test between the two methods in this review. Only one study by (28) reported a contrary view of studies done by ( 59…”
Section: Acquisition and Retention Of Skills After Cpr Trainingsupporting
confidence: 81%
“…(7,8) Amerikan Kalp Derneği (American Heart Association, AHA) önerilerine göre, KPR'nin geciktiği her dakika hayatta kalma oranı azalmaktadır. (9) Acil serviste çalışan hemşireler sağlık kurumlarında acil olayların sık yaşandığı saatlerde hastanın yanında bulunan ve çoğunlukla temel yaşam desteğini (TYD) ilk başlatan meslek grubudur. Kardiyak arrest sonrası hastaneden taburculuk oranları ise ortalama %8 civarındadır.…”
Section: Discussionunclassified
“…(13) Resüsitasyon uygulamasının kaliteli olmasında uluslararası kurallara dayalı düzenli eğitimlerin verilmesi ve standartlaştırılmış ekipmanların bulunması önemlidir. (9) Literatür incelemesi yapılan bir çalışmada simülasyon ile interaktif bir şekilde yapılan kısa, sık, tekrarlayan veya uygulamayı içeren bir öğretim planının, hemşirelerin zaman içinde KPR önceliklerini korumasını iyileştirmek için potansiyel bir strateji olabileceği vurgulanmıştır. (6) Hemşirelere yapılan teorik ve uygulamalı KPR eğitiminin etkililiğinin değerlendirilmesi hatalı uygulamaların düzeltilmesinde, geribildirim sağlanmasında ve öz yeterliliklerinin gelişmesinde önemli bir yer tutmaktadır.…”
Section: Discussionunclassified
“…Dari sudut ketekalan dalam kalangan pelajar, tahap pengetahuan pelajar yang diukur semula pada minggu kelapan telah menunjukkan penurunan dan ini menggambarkan bahawa kesemua pelajar gagal untuk mengekalkan tahap pengetahuan mereka selepas sesi intervensi dilaksanakan dalam tempoh dua bulan tersebut. Tanpa sebarang latihan dalam tempoh tersebut serta pengendalian kes-kes kecemasan yang melibatkan resusitasi, kebarangkalian berlakunya penurunan adalah tinggi dan kesan ini turut didokumentasikan dalam kajian tertentu yang melibatkan pengamal kesihatan menunjukkan tahap penurunan secara signifikan berlaku dalam tempoh tiga bulan selepas sesuatu latihan dilaksanakan (Bukiran et al, 2014;Ouseph et al, 2015). Sekiranya kadar penurunan dalam kalangan pengamal kesihatan adalah sekitar tiga bulan walaupun tugas hakiki mereka memerlukan pelaksanaan resusitasi, demikian jika dibandingkan dengan pelajar pendidikan yang diklasifikasikan sebagai orang awam sememangnya menggambarkan kadar penurunan dengan lebih cepat.…”
Section: Perbincanganunclassified